Traveling-wave thermoacoustic refrigerator with curved and tapered surfaces to minimize streaming - Mohsen Bahrami; Fathollah Ommi (Invention Disclosure)
The present article describes a traveling-wave thermoacoustic refrigeration system driven by a thermoacoustic heat engine. The coupled engine-refrigerator system consists of a resonator tube, which the thermoacoustic engine and thermoacoustic refrigerator are coaxially located at the extremities of the resonator tube. A thermoacoustic engine (refrigerator) consists of a regenerator, a hot (cold) heat exchanger, two ambient heat exchangers, and a thermal buffer tube. The cross-sectional area of the engine is lower than the resonator cross-sectional area, so a holder is employed to fix the engine inside the resonator tube. The hemispherical end caps, the inner ducts, and the outer ducts have variable cross-sectional areas designed to create a converging-diverging path for the acoustic wave from the outer space to the inner space of the coaxial ducts. Progressive companies on the lookout for a reliable, maintenance-free, environmentally-friendly cooling technology driven by any heat source are the potential customers of this scalable invention.